Epidemiological trends and age-period-cohort effects on lip and oral cavity cancer burden across the BRICS from 1992 to 2021 - Yu, Zhengrong; Wu, Yuhang; Cao, Yu; Cheng, Peiyu (Frontiers in Oncology, 2025)
BackgroundLip and oral cavity cancer (LOC) is one of the common malignant tumors of the head and neck, posing significant health and economic burdens. The BRICS, including Brazil, Russia, India, China, and South Africa, represent a large global population, presenting unique public health challenges. This study aims to evaluate the epidemiological trends and variations in the burden of LOC across BRICS in a timely manner.MethodsData on the number, all-age rate, age-standardized rate, and relative change in LOC incidence from 1992 to 2021 within BRICS were obtained from the Global Burden of Disease study (GBD) 2021, and we analyzed global and BRICS-specific LOC incidence trends over 30 years. Furthermore, age-period-cohort model was applied to estimate net drift, local drift, age, period and cohort effects between 1992 and 2021.ResultsIn 2021, the BRICS nations reported 194.74 thousand new LOC cases, constituting 46.2% of the global total. From 1992 to 2021, all BRICS countries witnessed a significant rise in LOC cases, with China leading at 259.06%. The age-standardized incidence of LOC increased by over 20% in the Russian Federation, India, and China, while Brazil and South Africa exhibited marginal changes (Brazil: 0.75%; South Africa: -7.87%). Rising LOC trends were prevalent across most age groups in China, India, and the Russian Federation, particularly affecting older adults (60-94 years). Age, period, and cohort effects were deteriorating in China and India, contrasting with improvements in Brazil and South Africa.ConclusionLOC incidence has increased across BRICS, with temporal trends not consistently aligning with economic growth and exhibiting significant variation among countries. Brazil’s experience highlights the efficacy of oral health and tobacco control measures in mitigating LOC, especially in fast-developing nations. Prevention should target men and elderly in China and India, and women in other areas.